Chronic ankle instability is not a unilateral phenomenon. A review of the literature based on neurophysiological and biomechanical fundamentals - Pinheiro De Sousa, Andreia Sofia (2021)
Chronic ankle instability (CAI) denotes the occurrence of repetitive bouts of lateral ankle instability, resulting in numerous ankle sprains. CAI may be influenced by several factors, including mechanical and functional deficits (Hertel, 2002). Mechanical ankle instability (MAI) can be attributed to pathological laxity, arthrokinematic changes, and/or syn ovial and degenerative changes (Hertel, 2000). Changes in the talus mo bility lead to an abnormal movement of the instantaneous axis of joint ro tation, resulting in altered proprioceptive input and altered motor control programmes (Denegar et al., 2002). Functional ankle instability (FAI) in corporates the recurrence of ankle instability and the sensation of joint instability due to sensorimotor deficits (Hertel, 2000). However, despite sensorimotor deficits, like impaired proprioception and delayed timing of peroneal muscle activation during short latency compensatory postur al responses, have been proposed, the mechanism behind CAI remains unclear. In fact, a more recent metanalysis performed by Munn et al. (2010), that pooled studies with a broad definitional criterion for CAI, showed that the peroneal reaction time was not impaired in this condition (Munn et al., 2010). Also, contradictory findings have been obtained as to proprioceptive impairments in CAI (Brown et al., 2004; Lentell et al., 1995; Lim et al., 2009; Nakasa et al., 2007). These contradictory findings could lie on the divergent selection criteria, but also on the reference used to identify the dysfunction. Several studies have considered the contrala teral limb to the CAI limb as a reference while others have considered subjects with no ankle sprain episodes. The use of the contralateral limb to the CAI limb as a reference lies on the premise that CAI is a unilateral phenomenon resulting from ipsilateral ankle sprain. However, this premise can be refuted using biomechanical, neurophysiological and motor control arguments.